High-energy diode-pumped alexandrite amplifier development with applications in satellite-based lidar - Coney,A; Damzen,M (Journal of the Optical Society of America B: Optical Physics, 2021)
Efficient, wavelength-tunable diode-pumped alexandrite laser systems offer the potential for a more versatile, satellite-based lidar source compared to fixed wavelength Nd:YAG systems and non-space compliant lamp-pumped alexandrite. In this paper, we develop a strategy to enable the high-energy operation required for atmospheric lidar based on an efficient diode-pumped Master-Oscillator Power-Amplifier (MOPA) system design. A novel multi-pass ‘diamond’ slab amplifier geometry is introduced alongside the experimental results of the world’s first diode-pumped alexandrite amplifier producing a gain of 2.13 in a demonstration system. A diode-pumped Q-switched alexandrite oscillator is presented with a record-highest pulse energy of 3.80 mJ. Detailed optimisation of a two-stage amplifier design is studied numerically and maximised with temperature, wavelength and pump pulse duration to produce 50 mJ pulse energy. This forms part of an optimised alexandrite MOPA design capable of high pulse energy, showing the future potential of diode pumped alexandrite for satellite-based atmospheric lidar.